AB0029 Characteristic patterns of hla presentation and t cell differentiation in adult-onset still's disease. (12th June 2018) - Kim, H.-A.; Jung, J.-Y.; Suh, C.-H.; Sohn, S.
Abstract : Background: The role of T cells in AOSD pathogenesis remains controversial. In autoimmune and auto-inflammatory diseases, such as rheumatoid arthritis (RA) and Behçet's disease, a human leukocyte antigen (HLA)-restricted T cell response to antigen has been shown to affect disease progression, with several HLA alleles strongly associated with disease severity. Objectives: In this study, we investigated the frequencies of cells presenting HLA-DP, DQ, and DR, as well as differentiated T cell populations including naïve and effector memory T cells in peripheral blood leukocytes (PBLs) of patients with AOSD. Frequencies of the markers were then compared based on clinical outcomes and disease activity, to better understand the role of these cell populations in the pathogenesis of AOSD. Methods: This study enrolled 14 active AOSD patients, 20 rheumatoid arthritis (RA) patients, and 20 healthy controls (HC). The percentage of surface-stained cells presenting HLA–DP, DQ, and DR alleles, and the proportions of differentiated T cell populations in peripheral blood leukocytes (PBLs) were measured by flow cytometry. Results: Patients with AOSD exhibited significantly higher percentages of lymphocytes presenting HLA-DP and HLA-DR, and lower percentages of cells presenting HLA-DQ, than patients with RA or HC. The proportions of CD4+, CD4 +CCR7+, CD4 +CD62L-, and CD8 +CD62L- cells in PBLs were decreased in patients with AOSD relative to patients with RA or HCs. In contrast, AOSD patients exhibited increased proportions of CD8 +naïve T cells in whole blood relative to patients with RA or HC. The proportions of CD4 +effector memory T cells, CD8 +naïve T cells, and CD8 +effector memory T cells in whole blood cells and CD4 +effector memory T cell in lymphocytes were significantly associated with systemic score. Conclusions: While the frequencies of CD4+, CD8+, CCR7+, CD4 +CCR7+, CD4 +CD62L-, and CD8 +CD62L- cells were significantly decreased in patients with AOSD, the frequency of CD8 +naïve T cells was elevated in patients with AOSD, and correlated with systemic score. Additional studies in a larger cohort of patients will be necessary to evaluate the role of these markers in the pathogenesis of AOSD. Disclosure of Interest: None declared